Gastropod-derived haemocyte extracellular traps entrap metastrongyloid larval stages of Angiostrongylus vasorum, Aelurostrongylus abstrusus and Troglostrongylus brevior. Issue 1 (December 2017) - Lange, Malin; Penagos-Tabares, Felipe; Muñoz-Caro, Tamara; Gärtner, Ulrich; Mejer, Helena; Schaper, Roland; Hermosilla, Carlos; Taubert, Anja
Abstract Background Phagocyte-derived extracellular traps (ETs) were recently demonstrated mainly in vertebrate hosts as an important effector mechanism against invading parasites. In the present study we aimed to characterize gastropod-derived invertebrate extracellular phagocyte trap (InEPT) formation in response to larval stages of important canine and feline metastrongyloid lungworms. Gastropod haemocytes were isolated from the slug speciesArion lusitanicus andLimax maximus, and the snailAchatina fulica, and exposed to larval stages ofAngiostrongylus vasorum, Aelurostrongylus abstrusus andTroglostrongylus brevior and investigated for gastropod-derived InEPT formation. Results Phase contrast as well as scanning electron microscopy (SEM) analyses of lungworm larvae-exposed haemocytes revealed ET-like structures to be extruded by haemocytes thereby contacting and ensnaring the parasites. Co-localization studies of haemocyte-derived extracellular DNA with histones and myeloperoxidase in larvae-entrapping structures confirmed classical characteristics of ETs. In vivo exposure of slugs toA. vasorum larvae resulted in InEPTs being extruded from haemocytes in the slug mucous extrapallial space emphasizing the pivotal role of this effector mechanism against invasive larvae. Functional larval entrapment assays demonstrated that almost half of the haemocyte-exposed larvae were contacted or even immobilized by released InEPTs. Overall, as reported for mammalian-derived ETs, different types of InEPTs were here observed, i.e. aggregated, spread and diffused InEPTs. Conclusions To our knowledge, this study represents the first report on metastrongyloid lungworm-triggered ETosis in gastropods thereby providing evidence of early mollusc host innate immune reactions against invading larvae. These findings will contribute to the better understanding on complex parasite-intermediate host interactions since different gastropod species bear different transmitting capacities for metastrongyloid infections.